CTIM-19. TEM-GBM: A PHASE I-IIA DOSE-ESCALATION STUDY DELIVERING IFN-Α WITHIN GLIOBLASTOMA MULTIFORME TUMOR MICROENVIRONMENT BY GENETICALLY MODIFIED TIE-2 EXPRESSING MONOCYTES. (12th November 2021) - Finocchiaro, Gaetano; Gentner, Bernhard; Marica, Eoli; Francesca, Farina; Capotondo, Alessia; Ferla, Valeria; Carrabba, Matteo; Cuccarini, Valeria; Meco, Francesco Di; Legnani, Federico; Pollo, Bianca; Saini, Marco; et al.
Abstract: Temferon is an ex vivo gene therapy consisting of autologous HSPCs genetically modified to deliver IFN-α2 within the tumor microenvironment (TME) by Tie-2 expressing macrophages. TEM-GBM is an open-label, Phase I/IIa dose-escalation study evaluating safety and efficacy of Temferon in up to 21 newly diagnosed GBM patients with unmethylated MGMT. Autologous HSPCs are transduced with a LVV encoding for IFN-a2 gene. As of 30 th April 2021, 18 patients have been enrolled; 13 received Temferon (D+0) with follow-up of 8 – 662 days. After conditioning and Temferon infusion, a rapid engraftment and hematological recovery occurred, with median neutrophil and platelet engraftment at D+13 and D+12, respectively. No dose limiting toxicities were reported. Temferon-derived cells were found within 14 days post treatment and persisted albeit at lower levels in the long-term. Five deaths occurred: one at +478, three at +322, +340 and +402 days due to PD, and the fourth at +60 due to complications following the conditioning regimen. Eight patients had PD (-12 to +239). SAEs include respiratory tract infections, pulmonary embolism, CMV and C.Diff infections, febrile neutropenia, hemiparesis, seizure, brain abscess, worsening of performance status and respiratory failure compatible with ASCT, concomitant medications and PD. Four patients underwent second surgery. Recurrent tumors had gene-marked cells present and increased expression of ISGs compared to diagnosis, indicative of local IFNa release by TEMs. In one patient, a stable lesion had a higher proportion of T cells and TEMs within the myeloid infiltrate and an increased IFN-response signature than in a progressing lesion. Characterization of T-cell immune repertoire suggests the expansion of tumor-associated clones. TME characterization by scRNA and TCR sequencing is ongoing. Interim results show that Temferon is well tolerated, with no dose limiting toxicities identified to date and provide initial evidence of potential immune system activation within the TME.